Efficacy and safety of weekly carfilzomib (70 mg/m2), dexamethasone, and daratumumab (KdD70) is comparable to twice-weekly KdD56 while being a more convenient dosing option: a cross-study comparison of the CANDOR and EQUULEUS studies. Issue 2 (28th January 2021) - Leleu, Xavier; Beksac, Meral; Chou, Takaaki; Dimopoulos, Meletios; Yoon, Sung-Soo; Prince, H. Miles; Pour, Ludek; Shelekhova, Tatiana; Chari, Ajai; Khurana, Monica; Zhang, Jianqi; Obreja, Mihaela; et al.
Abstract: The regimen of carfilzomib, daratumumab, and dexamethasone (KdD) shows activity in patients with relapsed/refractory multiple myeloma. KdD at the twice-weekly 56 mg/m 2 carfilzomib dose (KdD56) was used in the randomized phase 3 CANDOR study (NCT03158688), whereas KdD at the once-weekly 70 mg/m 2 carfilzomib dose (KdD70) was used in the phase 1 b EQUULEUS study (NCT01998971). We analyzed efficacy data from comparable CANDOR and EQUULEUS patients using inverse probability of treatment weighting (IPTW)–adjusted models. These weights were calculated from propensity scores derived to balance prespecified baseline covariates. The side-by-side and adjusted comparisons showed similar efficacy for overall response rates and progression-free survival in the two groups, with a series of sensitivity analyses showing consistent findings. Safety data were generally consistent with the known safety profiles of each individual drug. Once-weekly KdD70 is comparable to twice-weekly KdD56 in terms of efficacy and safety while being a more convenient dosing option.